Multimedia tutorial for the training of competences in the use of the computer aimed at the teachers of initial education (Revista Electrónica REDINE, 2018)
The present study was adjusted in the positivist paradigm, under a quantitative approach, supported by field research descriptive in the form of Special Project. The goal was to design a Multimedia Tutorial for Competenses Training in computer use. The study subjects were 45 teachers of early childhood education sector schools Nueva Segovia, Vicente Salias, Macario Yepez, Claret Community. For data collection was used  the survey technique and the instrument was a questionnaire dichotomous questions and response alternatives related to research. The validity was performed by expert judgment and for reliability carried out a test pilot and Kuder Richardson statistical calculation which is used in dichotomous items. The data were analyzed, interpreted and presented through graphs and frequency tables and percentages which casts the need to design a multimedia tutorial for skills training in computer use aimed at pre-school teachers, who despite not having the knowledge, skills and abilities to use the computer, hold the claim to incorporate as their own to integrate, strengthen and consolidate skills which, from the technological point of view, allow you to walk to the excellence of this first level of education.
Keywords: teacher training; skills; computer use